Lipase‐catalyzed process for biodiesel production: Protein engineering and lipase production. Issue 4 (17th December 2013) - Hwang, Hyun Tae; Qi, Feng; Yuan, Chongli; Zhao, Xuebing; Ramkrishna, Doraiswami; Liu, Dehua; Varma, Arvind
Abstract Biodiesel is an environment‐friendly and renewable fuel produced by transesterification of various feedstocks. Although the lipase‐catalyzed biodiesel production has many advantages over the conventional alkali catalyzed process, its industrial applications have been limited by high‐cost and low‐stability of lipase enzymes. This review provides a general overview of the recent advances in lipase engineering, including both protein modification and production. Recent advances in biotechnology such as in protein engineering, recombinant methods and metabolic engineering have been employed but are yet to impact lipase engineering for cost‐effective production of biodiesel. A summary of the current challenges and perspectives for potential solutions are also provided. Biotechnol. Bioeng. 2014;111: 639–653. © 2013 Wiley Periodicals, Inc.